2010
DOI: 10.1371/journal.pcbi.1001038
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Spatio-Temporal Input Characteristics by a CA1 Pyramidal Neuron Model

Abstract: The in vivo activity of CA1 pyramidal neurons alternates between regular spiking and bursting, but how these changes affect information processing remains unclear. Using a detailed CA1 pyramidal neuron model, we investigate how timing and spatial arrangement variations in synaptic inputs to the distal and proximal dendritic layers influence the information content of model responses. We find that the temporal delay between activation of the two layers acts as a switch between excitability modes: short delays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 115 publications
(169 reference statements)
2
24
0
Order By: Relevance
“…For the accurate recall of a memory pattern the dendritic inhibition in all three hippocampal regions (HC in DG, BC in CA3 and BSC in CA1) is instrumental by thresholding the GC and CA3-and CA1-PC firing, respectively. This result is in line with previous experimental results (Winson, 1978) and computational studies at both the single cell level, showing that inhibition is critical for gating and transforming the firing pattern of CA1 PCs (Pissadaki et al, 2010), and the network level (Cutsuridis et al, 2008;Cutsuridis, Cobb, et al, 2010;Cutsuridis et al, 2011;Cutsuridis & Hasselmo, 2012;Cutsuridis & Wenneckers, 2009;Kunec et al, 2005) showing that theta oscillations are implicated in the encoding and retrieval of memories (Cutsuridis & Hasselmo, 2012;Cutsuridis & Wenneckers, 2009;Cutsuridis et al, 2008;Cutsuridis, Cobb, et al, 2010;Hasselmo et al, 2002;Jensen & Lisman, 2005;Kunec et al, 2005) and disruption of them results in behavioral deficits (Winson, 1978).…”
Section: Factors Increasing Ca1 Pyramidal Neuron Dendritic Excitabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…For the accurate recall of a memory pattern the dendritic inhibition in all three hippocampal regions (HC in DG, BC in CA3 and BSC in CA1) is instrumental by thresholding the GC and CA3-and CA1-PC firing, respectively. This result is in line with previous experimental results (Winson, 1978) and computational studies at both the single cell level, showing that inhibition is critical for gating and transforming the firing pattern of CA1 PCs (Pissadaki et al, 2010), and the network level (Cutsuridis et al, 2008;Cutsuridis, Cobb, et al, 2010;Cutsuridis et al, 2011;Cutsuridis & Hasselmo, 2012;Cutsuridis & Wenneckers, 2009;Kunec et al, 2005) showing that theta oscillations are implicated in the encoding and retrieval of memories (Cutsuridis & Hasselmo, 2012;Cutsuridis & Wenneckers, 2009;Cutsuridis et al, 2008;Cutsuridis, Cobb, et al, 2010;Hasselmo et al, 2002;Jensen & Lisman, 2005;Kunec et al, 2005) and disruption of them results in behavioral deficits (Winson, 1978).…”
Section: Factors Increasing Ca1 Pyramidal Neuron Dendritic Excitabilitysupporting
confidence: 88%
“…Golding et al (2005) suggested that the distal synaptic inputs are likely only to be effective in causing CA1-PCs to fire action potentials when their distal dendrites are highly excitable. One way to increase excitability in these dendrites is by clustering of excitatory synaptic inputs, as previously shown by Poirazi et al (2003b) and Pissadaki, Sidiropoulou, Reczko, & Poirazi (2010).…”
Section: Factors Increasing Ca1 Pyramidal Neuron Dendritic Excitabilitymentioning
confidence: 89%
“…The R-type calcium current, however, has opposite effects, depending on its somatic or dendritic localization: dendritic modifications are proportional while somatic modifications are inversely proportional to the induction probability. The possible explanation for this observation is that R-type calcium channels contribute to bursting when located in the dendrites (Takahashi and Magee, 2009; Pissadaki et al, 2010) and to AHP when located at the soma. Thus, increasing R-type channel currents in the dendrites enhances local depolarization and perhaps contributes to dendritic spike generation, whereas increasing it in the soma does not contribute to dendritic events (Figures 5C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Although the differences in the AP latencies between ‘persistent’ and ‘no persistent’ trials were submillisecond, several studies suggest that they could still be decoded by downstream neurons [49], [50], [51]. This finding adds to the coding capabilities of the AP latency which has also been found to code for differences in spatiotemporal characteristics of the input in CA1 model neurons [48] as well as the location of sound in secondary auditory neurons [52].…”
Section: Discussionmentioning
confidence: 98%